2009
DOI: 10.1111/j.1751-1097.2008.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles of microRNAs in NIH3T3 Cells in Response to UVB Irradiation

Abstract: MicroRNAs (miRNAs) are known as a kind of small, noncoding RNA, which play an important role in mediating many biological processes such as development, cell proliferation and differentiation in plants and animals. Here we report the differential expression profiles of miRNAs and characterized putative target genes in NIH3T3 cells at a series of different time points after UVB irradiation (compared with no UVB irradiation). The relative expression of mature miRNA genes was determined by miRNA microarray techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 35 publications
(53 reference statements)
1
60
0
Order By: Relevance
“…Similarly, miR-18b overexpression promotes proliferation and loss of cell adhesion, and elevated levels of this miR correlates with reduced relapse-free survival in hepatocellular carcinoma (47). Finally, miR-365 expression is increased in breast cancer, as well as in response to UVB radiation (48,49). To our knowledge, there are no published clinical reports on miR and their role in predicting prostate cancer response to external beam radiotherapy or brachytherapy.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, miR-18b overexpression promotes proliferation and loss of cell adhesion, and elevated levels of this miR correlates with reduced relapse-free survival in hepatocellular carcinoma (47). Finally, miR-365 expression is increased in breast cancer, as well as in response to UVB radiation (48,49). To our knowledge, there are no published clinical reports on miR and their role in predicting prostate cancer response to external beam radiotherapy or brachytherapy.…”
Section: Discussionmentioning
confidence: 85%
“…miRNAs are evolutionarily conserved small noncoding RNAs that regulate gene expression and play important roles in diverse biological functions, including cell differentiation, proliferation, apoptosis, tumorigenesis, and the immune response (12)(13)(14)(15)(16)(17). Previous studies have shown that miRNA expression profiles change in response to UVB irradiation, and these changes were most pronounced within the first few hours following UVB exposure (23,24). Thus, we wanted to determine whether miRNA is involved in UVB-induced melanocyte dendricity at an early stage.…”
Section: Uvb Irradiation Promotes Melanocyte Dendricitymentioning
confidence: 99%
“…The miRNA expression profiles of UV-irradiated cells have been investigated using miRNA microarrays, and in one such study, differential miRNA expression profiles were found in UVBirradiated NIH 3T3 cells compared with nonirradiated cells (23). The miRNA expression changes were most pronounced within the first hours following UVB irradiation, suggesting that miRNAmediated gene regulation operates earlier than most transcriptional responses (24).…”
mentioning
confidence: 99%
“…Enlightening findings on the microRNA expression profile have been obtained in mouse fibroblast cell line NIH3T3 irradiated with UV-B. UV-B irradiation resulted in robust changes in the microRNA expression profile including the upregulation of let-7a, miR-21, and miR-24 and the downregulation of miR-465 (Guo et al, 2009). Subsequent work on microRNA expression in primary human keratinocytes exposed to UV-A or UV-B radiation revealed that UV-A induces miR-21, miR-203, and miR-205, whereas UV-B moderately induces miR-203, reduces miR-205 and had no effect on miR-21 (Dziunycz et al, 2010).…”
Section: Micrornasmentioning
confidence: 99%